MANIFESTAÇÕES CLÍNICAS SUGESTIVAS DE DEPRESSÃO NOS PACIENTES ATENDIDOS COM DOENÇA FEBRIL EM CAMPO GRANDE (MS) E DOURADOS (MS) - Hugo Miguel Ramos Vieira (2021)
Introduction: In Brazil, a country with a high temperature, favorable to the development of the vector, the mosquito has already become a problem, because of not only Dengue, Zika and Chikungunya, which plague some Brazilian regions. In the last fifty years, it has been possible to observe that the febrile illness, worldwide, has increased dramatically and exponentially. According to the World Health Organization, about more than 4.5 million people are living in areas considered at risk to be infected, and they can develop the disease. In Brazil, transmission has been ongoing since 1986, when the first outbreaks were recorded. Only in 2013 was it possible to observe an increase in cases, with a total of two million reported cases, becoming a disease that should not be neglected by public health. Objectives: to identify patients seen in Campo Grande (MS) and Dourados (MS) with febrile symptoms and their possible depressive symptoms. Methodology: This is a cohort study with patients who obtained a proven diagnosis of clinical-epidemiological and laboratory dengue (ELISA; RT-PCR AND NS1), seen at the SUS network in the cities of Campo Grande (MS) and Dourados (MS). The collection period was from 2018, starting from April, to September 2019. The CES-D instrument was used to make the possible diagnosis of depression. Results: In the 115 Dengue-positive participants, a V0 sample was found with 63.5% who developed symptoms for depression. In the V14 period, patient is positive for Dengue totaled 37.4% and these patients did not develop according to the casuistry of the instrument used depression and totaled 62.6%. Patients with positive febrile illnesses had no history of Diabetes Mellitus. Discussion: It was possible to verify in this study that depression is a mood disorder whose symptom together brings suffering and, mainly, social and occupational damage to the analyzed sample. The results of this study are consistent with Brazilian socio-cultural characteristics by highlighting the female gender, as the main characteristic, as the woman remains a large period of the day inside or outside the home and, still, it is possible to consider that the male gender presents a lower percentage in the search for the health service. compared to females and, probably, that is why there is a lower amount of underreporting in relation to males. In relation to depression, the positive and somatic affects among patients at V0 were observed due to the presence mainly of myalgia and arthralgia, which can be considered one of the symptoms beginning to increase the score in the depressive symptom. The stress of illness intensifies the symptoms of chronic fatigue, which decrease the quality of life of these participants. Conclusion: There is a significant direct relationship between the numbers of patients who developed depression in the process of becoming ill with febrile illnesses. Keywords: Dengue. Zika. Chikungunya. Immune response. Depression. CES-D.